2018
DOI: 10.1371/journal.ppat.1006944
|View full text |Cite
|
Sign up to set email alerts
|

Infant transmitted/founder HIV-1 viruses from peripartum transmission are neutralization resistant to paired maternal plasma

Abstract: Despite extensive genetic diversity of HIV-1 in chronic infection, a single or few maternal virus variants become the founders of an infant’s infection. These transmitted/founder (T/F) variants are of particular interest, as a maternal or infant HIV vaccine should raise envelope (Env) specific IgG responses capable of blocking this group of viruses. However, the maternal or infant factors that contribute to selection of infant T/F viruses are not well understood. In this study, we amplified HIV-1 env genes by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 67 publications
3
36
1
Order By: Relevance
“…V H 1-69 was the most frequently occurring allelic variant of Env-specific IgG in both nontransmitting and transmitting mothers. To examine the V H mutation differences among the Envspecific IgG MAbs obtained from nontransmitting and transmitting mothers, we utilized a previously described permutation test which accounts for multiple measurements (i.e., multiple MAbs obtained per patient) from each patient (25). We detected no significant difference in the V H somatic mutation levels of Env-specific IgG MAbs obtained from nontransmitting and transmitting HIV-infected mothers (P ϭ 0.22) (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…V H 1-69 was the most frequently occurring allelic variant of Env-specific IgG in both nontransmitting and transmitting mothers. To examine the V H mutation differences among the Envspecific IgG MAbs obtained from nontransmitting and transmitting mothers, we utilized a previously described permutation test which accounts for multiple measurements (i.e., multiple MAbs obtained per patient) from each patient (25). We detected no significant difference in the V H somatic mutation levels of Env-specific IgG MAbs obtained from nontransmitting and transmitting HIV-infected mothers (P ϭ 0.22) (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…HIV can escape from host autologous-virus-neutralizing antibodies via several mechanisms, which include shifting Env glycans, epitope sequence alteration, and conformational masking of proximal and distal epitopes (23,24). We recently reported that infant-transmitted founder (infant-T/F) viruses are more neutralization resistant to paired maternal-plasma viruses than to nontransmitted maternal-plasma viruses, indicating that a potential mechanism by which infant-T/F viruses are selected is via the escape from maternal-plasma autologous-virus-neutralizing antibodies (25). A better understanding of the evolution dynamics of maternal neutralizing antibodies and maternal autologous viruses, which is the precursor pool of the infant-T/F viruses, will be important to design immunologic strategies to block the vertical transmission of HIV.…”
mentioning
confidence: 99%
“…SGA. Single-genome amplification (SGA) of plasma virus was done as described previously (63). The primer used for cDNA preparation was SHIVEnv.R3out.…”
mentioning
confidence: 99%
“…On the other hand, non-transmitted (NT) variants constitute a genetically diverse population of HIV-1 isolates that are sensitive to maternal antibodies 27 . Studies have shown that the viral variants in the transmitting partner were different from the transmitted founder virus in the newly infected partner 25 .…”
Section: Definition Of Tf and Nt Variantsmentioning
confidence: 99%